A Facile Method for Heteroepitaxial Growth of Homogeneous 3C-SiC Thin Films on Both Surfaces of Suspended Si Wafer by Conventional Chemical Vapor Deposition. (14th December 2016) - Liu, X. F.; Yan, G. G.; Shen, Z. W.; Wen, Z. X.; Tian, L. X.; Zhao, W. S.; Wang, L.; Guan, M.; Zhang, F.; Sun, G. S.; Zeng, Y. P.
Abstract : Although epitaxial growth of Si films on both surfaces of silicon wafer (epi-Si/Si-wafer/epi-Si) can be realized in foundry by means of mounting certain amounts of silicon wafers in a boat in commercial specialized chemical vapor deposition equipment (s-CVD), for its counterpart epi-SiC/Si-wafer/epi-SiC, neither is it readily realized in s-CVD, nor is it easily achieved in conventional chemical vapor deposition equipment (c-CVD) which is generally used for growth of 3C-SiC on single surface of silicon wafer (epi-SiC/Si-wafer). Since the growth of epi-SiC/Si-wafer/epi-SiC in one run is more efficient, and is anticipated, in this work, we demonstrated a facile method for growth of epi-SiC/Si-wafer/epi-SiC in c-CVD. The Si wafer was double-side polished and mounted in a suspension mode on the susceptor in the c-CVD chamber. It was found that homogeneous 3C-SiC(100) films were heteroepitaxially grown on both surfaces of the suspended Si(100) wafer simultaneously. The structural and electrical properties of the obtained 3C-SiC films on both surfaces were investigated by means of SEM, XRD, Raman and J-V measurements. Results showed that each film was uniform and continuous, with same trend of slight degradation from the inner to the outer region of the wafer. This indicated a possible way of making mass production of high quality 3C-SiC films on Si wafers in one run in c-CVD for the potential applications such as sensors, with working principle based on voltage drop difference of two back-to-back diodes on epi-SiC/Si-wafer/epi-SiC, or graphene growth from epi-SiC/Si-wafer/epi-SiC templates.